PENYELESAIAN SENGKETA PEMILU; DARI KEWENANGAN SISA MENJADI KEWENANGAN MAHKOTA DALAM PERSPEKTIF SEJARAH HUKUM - Yulianto (Jurnal Keadilan Pemilu, 2022)
Election dispute resolution rules that apply to the execution of elections do not suddenly appear. It is the outcome of a protracted search for a democratic electoral system. As a result, it is essential to investigate the history and development of Indonesia's election dispute settlement mechanisms as well as the legal standards that have been established in the past. This is the normative study and has a historical legal perspective. According to the study's findings, Bawaslu is the sole authority responsible for resolving election-related disputes, and his rulings are final and binding. It is possible to implement Bawaslu's decision without relying on the judgment of other organizations. It is fair to assume that Bawaslu's authority in settling issues about the electoral process has changed from what was once known as "residual authority" to being "royal authority."